2019
DOI: 10.3390/genes10060479
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Fields, Genomic Instability and Cancer: A Systems Biological View

Abstract: This review discusses the use of systems biology in understanding the biological effectsof electromagnetic fields, with particular focus on induction of genomic instability and cancer. Weintroduce basic concepts of the dynamical systems theory such as the state space and attractors andthe use of these concepts in understanding the behavior of complex biological systems. We thendiscuss genomic instability in the framework of the dynamical systems theory, and describe thehypothesis that environmentally induced g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…However, we cannot fully exclude the possibility that wEMFs affect specific repair processes under specific conditions, as reported for instance for nucleotide excision repair in cancerous p53 negative cells [56]. Besides directly damaging DNA or perturbing DNA repair capacity, wEMFs might trigger a general stress response in cells, which then modulates cell behavior in the presence of additional stressors such as genotoxic agents or unfavorable cell culture conditions [61]. If that was the case, it is not surprising that the complexity of the interactions of environmental factors, combined with the variable genetic make-up and physiological state of cells, will generate cell type-specific [48,54] and difficult to reproduce experimental outcomes [6,20].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, we cannot fully exclude the possibility that wEMFs affect specific repair processes under specific conditions, as reported for instance for nucleotide excision repair in cancerous p53 negative cells [56]. Besides directly damaging DNA or perturbing DNA repair capacity, wEMFs might trigger a general stress response in cells, which then modulates cell behavior in the presence of additional stressors such as genotoxic agents or unfavorable cell culture conditions [61]. If that was the case, it is not surprising that the complexity of the interactions of environmental factors, combined with the variable genetic make-up and physiological state of cells, will generate cell type-specific [48,54] and difficult to reproduce experimental outcomes [6,20].…”
Section: Discussionmentioning
confidence: 85%
“…We, therefore, conclude that the CA, designed to measure DNA damage on the single cell level, may have limitations in monitoring cellular wEMF responses and produce weak positive results in one setup and a negative result in another, depending on the experimental conditions and applied method of analysis and statistic [38,47,64,65]. In our opinion, the cell culture method appears very critical for the determination of the genotoxic potential of wEMF exposure, as cellular stress might be induced to a variable extent, which modulates wEMF-dependent responses [61]. For instance, we were not able to measure increased DNA damage in GSM-217Hz-exposed HTR-8/SVneo cells, using complete standard growth medium (Figures 1 and 4), whereas a weak tendency ( Figure S16) and significantly increased DNA damage [22] were apparent, when the same cells were grown without serum at high cell density.…”
Section: Discussionmentioning
confidence: 99%
“…9 Ten out of 12 review studies included in the review suggested possibility of linkage of EMF with cellular pathways like apoptosis and other cellular regulatory mechanism which may lead to carcinogenesis. [10][11][12][13][14][15][16][17][18][19] One study also reported increased reactive oxygen species on exposure to EMF in human cell lines leading to cellular damage. 11 However, two review articles reported unlikely or inconsistent findings of any effect of EMF exposure on cognitive functions and brain tumours.…”
Section: Resultsmentioning
confidence: 99%
“…Heat dissipation depends on three mechanisms: transfer, convection and radiation of thermal energy (18). Humans and animal's body tissues are very sensitive to electromagnetic radiation in terms of heat genesis due to the absorption and conversion of electromagnetic energy to heat energy by translational and vibrational excitation of the atoms inside the cell leading to heat generation (19)(20)(21). The generation of heat in the tissues is connected to the amount of radiation energy absorbed, which depends on the radiation frequency and exposure time in a sufficient degree of tissue warm-up leading to cellular dysfunction (22,23).…”
Section: Discussionmentioning
confidence: 99%